Kluster Gen Biosintetik (NRPS/PKS) Pada Bakteri Sedimen Mangrove Pantai Tirang Semarang Indonesia - Barra Muzaffar Widayat; Delianis Pringgenies; Wilis Ari Setyati (Jurnal Kelautan Tropis, 2024)
This study aims to explore biosynthetic gene clusters and antibacterial activity in mangrove sediment bacteria at Tirang Beach, Semarang, Central Java. Research methods include isolating bacteria from seagrass sediments, antibacterial testing against S. aureus and E. coli bacteria, identifying bacteria using the DNA method, and testing the presence of biosynthetic gene clusters. The results showed that the mangrove sediment bacterial isolate with the isolate code B.26.ST.3.4 had the highest antibacterial activity with a value of 28.05 ± 0.9192 against the pathogen E. coli and 23.45 ± 10.2530 against the pathogen S. aureus. Apart from that, there are two other isolates that also have antibacterial activity. Based on bacterial DNA identification, mangrove sediment bacteria that have potential as antibacterials are Bacillus velezensis (B.9.ST.1.4), Bacillus subtilis (B.13.ST.2.2), and Bacillus amyloliquefaciens (B.26.ST.3.4). These three isolates have the NRPS gene, and isolate B.9.ST.1.4 also has the PKS-II gene, while isolate B.26.ST.3.4 has the PKS-I gene. This discovery provides a deeper understanding of the antibacterial potential of mangrove sediment bacteria at Tirang Beach, Semarang. This information can be used to develop natural antibiotics that are more effective and have the potential to fight bacterial infections that are increasingly resistant to conventional antibiotics. The conclusion is that bacteria have potential as antibacterials from mangrove sediment bacteria at Tirang Beach, Semarang through isolation and identification of bacteria. Isolate B.26.ST.3.4 has the highest antibacterial activity against E. coli and S. aureus pathogens. Apart from that, Bacillus velezensis, Bacillus subtilis, and Bacillus amyloliquefaciens also have antibacterial potential. The NRPS gene was found in all three isolates, while isolate B.9.ST.1.4 also had the PKS-II gene and isolate B.26.ST.3.4 had the PKS-I gene. This discovery can provide a deeper understanding of the natural antibiotic potential of mangrove sediment bacteria and can be the basis for further development in the pharmaceutical field.